The influence of investment indirect and direct expenditure work force and education on economic growth in North Sumatera - Sischa Mahyasari Br Rangkuti; Raina Linda Sari; Irsyad (Institute of Computer Science (IOCS), 2023)
Background: Economic development is an important issue of a country's economy which has been planned every year on an ongoing basis in the long term towards a more reversed state for a certain period. Aims: This study aims to analyze the influence of investment, indirect and direct spending, labor force, and education on economic growth in North Sumatra. Methods: This study used secondary data from 1990 to 2020. The analysis Model used is ECM (Error Correction Model). Results: Based on the results of research on short - term and long-term investment variables have a positive and significant effect in North Sumatra, variables of direct spending and indirect spending have a positive and significant effect in the short and long term in North Sumatra. Conclusions: Labor force variables have a positive and significant effect in the short and long term in North Sumatra. and educational variables have a positive and significant effect on economic growth in North Sumatra. The implication of this study shows that both financial investment and simultaneous positive effects have a significant positive effect on the realization of PMDN value on economic growth in the North Sumatra with an investment rate of = 5%